2017
DOI: 10.5664/jcsm.6378
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Improves Selected Metabolic Parameters but Not Neuropsychological or Quality of Life Indices in OSA: A Pilot Study

Abstract: Study Objectives: Our group and others have reported a high rate of vitamin D deficiency in obstructive sleep apnea (OSA), where vitamin D levels (25(OH) D) correlate negatively with OSA severity and some of its associated metabolic alterations. Data regarding vitamin D supplementation in OSA are lacking. We wanted to evaluate the effect of vitamin D 3 supplementation on OSA symptoms and metabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Previous studies have primarily assessed vitamin D levels in patients with OSA (Archontogeorgis et al ., ; Barcelo et al ., ; Erden et al ., ; Kerley et al ., , ; Mete et al ., ; Salepci et al ., ; Toujani et al ., ), whereas markers of bone turnover have not been studied extensively in this patient group (Terzi and Yilmaz, ). Barcelo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have primarily assessed vitamin D levels in patients with OSA (Archontogeorgis et al ., ; Barcelo et al ., ; Erden et al ., ; Kerley et al ., , ; Mete et al ., ; Salepci et al ., ; Toujani et al ., ), whereas markers of bone turnover have not been studied extensively in this patient group (Terzi and Yilmaz, ). Barcelo et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kerley et al . () showed in a group of patients with OSA that supplementation with vitamin D improved several metabolic variables, such as decreases in both low‐density lipoprotein and lipoprotein‐associated phospholipase A2, as well as trends toward decreased fasting glucose and increased high‐density lipoprotein. However, as we only observed a modification of 25(OHD) and bone turnover markers in certain subsamples of patients and with increased CPAP treatment time frames, this might indicate that OSA impacts energy metabolism only in certain patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, information on other sleeprelated disturbances or disorders, including sleep apnoea, were not collected in our study. Several studies have reported that sleep apnoea was associated with lower serum 25OHD levels [79][80][81][82][83][84][85][86][87]. Furthermore, it remains possible that the associations between sleep and vitamin D status may be due to associations with poor health [88], including unmeasured confounding variables such as depression [89] and musculoskeletal pain [39] or inflammation [90]; these unmeasured confounding variables may differ by sex especially in Chinese populations.…”
Section: Plos Onementioning
confidence: 99%
“…The increase in serum 25OHD levels and decrease in both sleepiness and AHI were mainly observed in the obese patients compared to non-obese OSA men treated with CPAP. A pilot study assessing Caucasian OSA individuals submitted to cholecalciferol supplementation (4000 IU/ day) during 15 weeks (Kerley et al 2017) showed an increase in 25OHD serum levels in the supplemented group vs placebo (100.8 ± 39.9 nmol/L × 43.0 ± 21.4 nmol/L, respectively), and a decrease in metabolic parameters such as low-density lipoprotein (LDL) and lipoproteinassociated phospholipase A2 (Lp-PLA2). Some subjects from both groups used CPAP, but the data were not controlled, hampering the interpretation about the benefits of the supplementation since there is current evidence that CPAP use can increase 25OHD levels (Liguori et al 2015).…”
Section: :1mentioning
confidence: 99%